High dynamic range real-time 3D measurement based on Fourier transform profilometry. (June 2021) - Liu, Yanzhao; Fu, Yanjun; Zhuan, Yuhao; Zhong, Kejun; Guan, Bingliang
Highlights: A high dynamic range real-time 3D measurement is proposed. The proposed method can measure the dynamic objects with shiny surfaces. Three images with different intensities are separated from one color image. Compared with the other methods, the proposed method requires fewer images. Abstract: The high dynamic range (HDR) fringe projection technique is widely used to measure the three-dimensional (3D) shapes of objects with shiny surfaces; however, it tends to compromise when measuring the dynamic objects. To reduce the number of images and improve the real-time performance, a Fourier transform profilometry (FTP)-based method that can increase the dynamic range for real-time 3D measurement is proposed. Firstly, single-color patterns are projected onto the measured object, and one captured color image can be separated into three monochrome images with different intensities by taking advantage of the different responses of R, G, and B channels. Second, the HDR fringe pattern is generated by compositing three monochrome images, and then processed by the background-normalized algorithm to obtain the final fringe pattern. Subsequently, FTP is employed to retrieve the phase map and obtain the 3D shape. The experimental results demonstrated that the proposed method can measure the dynamic objects with shiny surfaces in real-time 3D measurement system.